Pharmacokinetics, pharmacodynamics, and safety of lesinurad, a selective uric acid reabsorption inhibitor, in healthy adult males - Shen Z; Rowlings C; Kerr B; Hingorani V; Manhard K; Quart B; Yeh LT; Storgard C (Dove Medical Press, 2015)
Zancong Shen, Colin Rowlings, Brad Kerr, Vijay Hingorani, Kimberly Manhard, Barry Quart, Li-Tain Yeh, Chris Storgard Ardea Biosciences, Inc. (a member of the AstraZeneca group), San Diego, CA, USA Abstract: Lesinurad is a selective uric acid reabsorption inhibitor under investigation for the treatment of gout. Single and multiple ascending dose studies were conducted to evaluate pharmacokinetics, pharmacodynamics, and safety of lesinurad in healthy males. Lesinurad was administered as an oral solution between 5 mg and 600 mg (single ascending dose; N=34) and as an oral solution or immediate-release capsules once daily (qday) between 100 mg and 400 mg for 10 days under fasted or fed condition (multiple ascending dose; N=32). Following single doses of lesinurad solution, absorption was rapid and exposure (maximum observed plasma concentration and area under the plasma concentration–time curve) increased in a dose-proportional manner. Following multiple qday doses, there was no apparent accumulation of lesinurad. Urinary excretion of unchanged lesinurad was generally between 30% and 40% of dose. Increases in urinary excretion of uric acid and reductions in serum uric acid correlated with dose. Following 400 mg qday dosing, serum uric acid reduction was 35% at 24 hours post-dose, supporting qday dosing. A relative bioavailability study in healthy males (N=8) indicated a nearly identical pharmacokinetic profile following dosing of tablets or capsules. Lesinurad was generally safe and well tolerated. Keywords: urinary excretion, urate lowering, URAT1, single and multiple doses, food effect, clearance